Communities Beyond Society: Divergence of Local Prehistories on the Bothnian Arc, Northern Europe - Hakonen Aki (De Gruyter, 2021)
This article presents a comparison of material records of two nearby regions on the coast of the Bothnian Bay. The timeframe is 5300–2000 BCE. The focus is on regional differences, which indicate a schizmogenesis of communal identities. The study calls for a reorientation of research concerning Fennoscandian prehistory. More attention should be paid to localized prehistories. It is argued that when prehistoric society is used as a fundamental group category, especially in the context of forager communities, the modern concept of state society distorts the underlying framework. Focusing on the regional level by constructing local prehistoric narratives limits the anachronistic effect and allows the proliferation of local communal identities. Such local prehistories, when collated and compared, offer a pathway to understanding prehistoric stateless societies, which are misrepresented by simplistic material cultural zones and the inherent homogeny ingrained within the concept of society. In this paper, the analysis is focused on practices representing local traditions. Two divergent themes that arise from the local prehistoric narratives are the Late Mesolithic use of local stone materials and regional changes in Neolithic dwelling forms.